2019
DOI: 10.2147/imcrj.s192764
|View full text |Cite
|
Sign up to set email alerts
|

<p>Subcutaneous sparganosis mimicking soft tissue tumor: a case report</p>

Abstract: Background Sparganosis is a rare parasitic disease of humans caused by invasion of human tissue by plerocercoid tapeworm larvae (spargana) of the genus Spirometra species. This parasite commonly invades subcutaneous tissue but can appear in any tissue of the body. Case presentation Here, we report a case of a 33-year-old woman presented with a migrating painful swelling and erythema in right thigh for 6 months, which was initially misdiagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Instead, studies focused on prevalence or molecular identification to understand a broader objective of host species conservation or parasite biogeographic distribution ( Kuchta et al, 2021 ; Wang et al, 2011 , 2014 ; Yamasaki et al, 2021 ). However, we note that there are reports of sparganosis resulting in severe illness or death in other vertebrates ( Buergelt et al, 1984 ; Drake et al, 2008 ; Hwang et al, 2019 ; Kikuchi and Maruyama, 2020 ).…”
Section: Discussionmentioning
confidence: 66%
“…Instead, studies focused on prevalence or molecular identification to understand a broader objective of host species conservation or parasite biogeographic distribution ( Kuchta et al, 2021 ; Wang et al, 2011 , 2014 ; Yamasaki et al, 2021 ). However, we note that there are reports of sparganosis resulting in severe illness or death in other vertebrates ( Buergelt et al, 1984 ; Drake et al, 2008 ; Hwang et al, 2019 ; Kikuchi and Maruyama, 2020 ).…”
Section: Discussionmentioning
confidence: 66%
“…When humans are infected, the larvae tend to migrate to subcutaneous tissues, muscle, breast, pleural cavity, lungs, urogenital viscera, abdominal viscera, or the central nervous system. 4,9 The most common clinical presentation is a mobile, slow-growing, mostly fixed but occasionally migratory, subcutaneous nodule or mass with a diameter of 0.5-5 cm, which is often confused with benign growths such as fibromas, lipomas, or cysts. The lesion itself may be erythematous, and it can be itchy or painful.…”
Section: Discussionmentioning
confidence: 99%
“…8b we have shown three parameterizations for the whitecap coverage from the literature overlying the in situ measurements (Monahan & Ó Muircheartaigh, 1980;A. Callaghan et al, 2008;Hwang, 2018). We used the AIC to compare the existing parameterizations shown in Fig.…”
Section: Meta-analysis Of Whitecap Datamentioning
confidence: 99%
“…In a bulk flux model of the air-sea exchange of heat, Andreas et al (2015) showed that these large, "shear" sea-spray droplets accounted for fluxes of sensible and latent heat on the same order of magnitude as fluxes directly from the ocean-atmosphere interface at high wind speeds (U 10 > 15 m s −1 ). Observations and model simulations have shown that the rate of momentum transferred from the atmosphere to the ocean starts to decrease after a critical threshold wind speed is passed (30 m s −1 ; (Powell et al, 2003;Bao et al, 2011;Hwang, 2018)). Theoretical work has suggested that this change is driven by the exchange of sensible heat between the largest droplets and the atmosphere, which become more abundant at high wind speeds (Bao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%